5-HTP Efficacy and Contraindications [Expression of Concern] - Hinz M (Dove Medical Press, 2020)
Hinz M, Stein A, Uncini T. Neuropsychiatr Dis Treat.  2012;8:323– 328. The Editor-in-Chief and Publisher of Neuropsychiatric Disease and Treatment wish to issue an Expression of Concern for the published article. Concerns have been raised regarding the alleged undisclosed competing interests of some of the authors and alleged excessive self-citation for the published article. Neuropsychiatric Disease and Treatment would like to alert readers of this while our investigation is still ongoing and we will provide an update following the conclusion of our investigation. The authors have been informed of these concerns and of our investigation. Read the original article